Mandating flexible work arrangements without legislation: A discourse on the case of Singapore - Tan, Adrian; Nguyen, Tien (2025)
In the context of the recently introduced “Tripartite Guidelines on Flexible Work Arrangements Requests” in Singapore in 2024, this study aims to critically examine and discuss the implementation of the mandate of flexible work arrangements without a formal legislation in Singapore. It is opined that Singapore workers continue to face issues of acceptance by their employers for their requests and needs for flexible work arrangements; however, it is also acknowledged that the implementation of the guidelines is still in an infancy stage. The evidence suggests that if the guidelines for flexible work arrangements are not handled properly by employers, such guidelines and even the flexible work arrangement itself might hurt the exact groups that they are supposed to help. Hence, the research questions if the mandate of flexible work arrangements without a formal legislation and instead leaving the compliance to the guidelines to corporate responsibility and sensibility, works for the well-being intent of employees and for the greater good of society. Acknowledging that flexible work arrangements are not a one-size-fits-all solution for work-life tensions, the research also emphasizes a holistic approach to the implementation of flexible work arrangements, one that focuses not only on policy and structural changes but also on cultural and mindset changes for a transparent, equitable, and effective implementation and governance of flexible work arrangements in Singapore.